ANALYSIS OF FACTORS AFFECTING THE MARKET SHARE OF ISLAMIC BANKS IN INDONESIA (The Indonesian Journal of Business Administration, 2019)
Islamic Bank is a bank that conducts operational activities based on sharia principles. In Indonesia it is known as sharia banking, sharia principles are agreements based on Islamic law. One essential Islamic banking activity is the distribution of funds. Fund distribution in conventional banks called credit, while the distribution of funds in Islamic banks called financing. The progress of the market share of Islamic banking is inseparable from the development of third party funds (TPF), the more third party funds (TPF), the more opportunities to channel funds to customers. Important thing for sharia banking to increase market share in the macro economy is the use of various sharia financial products and instruments that can strengthen the relationship between the real sector and the banking sector.This aims of this study was to determine the factors that influence market share in Islamic Banks in Indonesia. Data sourced from the Financial Services Authority (OJK) quarterly reports of Islamic Banks and Conventional Banks in Indonesia from March 2008 - December 2018. The sampling method was used purposive sampling, with data analysis used was analysis Ordinary Least Square (OLS) panel data regression.The result of research independent variables market share of total assets, and number of office market share has a significant influence on the financing market share and market share of Third Party Fund, while ROA and FDR proportion has a significant influence on Market Share Third Party Fund. Based on the results of testing the hypothesis with the T- test and F- test on market share Financing, the results obtained F-count > F-table (14.989> 2.112) and probability 0.000 <0.05, then Ho is rejected and Ha is accepted and the result Market share Third Party Fund F-count> F-table ( 9.856 > 2.112) and probability 0.000 <0.05, then Ho is rejected and Ha is accepted. The result of determination coefficient obtained which is shown by the value of r square as much as  0.7987 or 79.87%, its shows that as much as 79.87% contributed effect from all independent variable towards fund market share, while the remaining is as much 20.13% is a contribution from other variable outside this research. The result of determination coefficient is obtained which is shown by the value of r-square as much as 0.7229 or 72.29%, its shows that as much as 72.29% is contribution from the effect of all independent variable towards third party fund equivalence, while the remaining as much as 27.71% is a contribution from another variable outside this research.Keywords : Market Share, total assets, equivalence Third Party Fund, operational costs, CAR, BOPO, FDR, NPF, number of office, ROA, Financing